Discrete choice experiments: a primer for the communication researcher - Reynolds, Reed M.; Popova, Lucy; Yang, Bo; Louviere, Jordan; Thrasher, James F. (Frontiers in Communication, 2025)
Experiments are widely used in communication research to help establish cause and effect, however, studies published in communication journals rarely use discrete choice experiments (DCEs). DCEs have become a mainstay in fields such as behavioral economics, medicine, and public policy, and can be used to enhance research on the effects of message attributes across a wide range of domains and modalities. DCEs are powerful for disentangling the influence of many message attributes with modest sample sizes and participant burden. The benefits of DCEs result from multiple design elements including stimulus sets that elicit direct comparisons, blocked and/or fractional factorial structures, and a wide range of analytic options. Though sophisticated, the tools necessary to implement a DCE are freely available, and this article provides resources to communication scholars and practitioners seeking to add DCEs to their own methodological repertoire.